Euretina in a blink. (February 2013) - Golan, Shani; Goldstein, Michaella; Loewenstein, Anat
The 12th Euretina Congress Milan, Italy, 6–9 September 2012 The congress provided a chance for retina specialists all over the world to listen and learn from international world-leading experts in retina sharing their experience and knowledge. Main sessions, free paper presentation sessions, instructional courses and wetlabs took place throughout the 4-day meeting. In addition, joint symposia with both ESCRS and WCPOS added an exciting dimension to the program.